2018
DOI: 10.1109/tdei.2018.007310
|View full text |Cite
|
Sign up to set email alerts
|

Electrical tree growth and partial discharge in epoxy resin under combined AC and DC voltage waveforms

Abstract: The effect of DC bias on electrical tree growth and partial discharge (PD) characteristics in epoxy resin (Araldite LY ® 5052/Aradur® HY 5052 supplied by Huntsman) is investigated using three waveforms: AC, AC with positive DC bias, and AC with negative DC bias. Needle-plane samples are used. Tree growth is shown to be accelerated by the combined effect of DC and 50 Hz AC, beyond the AC growth rate. Positive and negative DC biased tests result in 62% and 54% reductions in average time to breakdown, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 19 publications
(30 reference statements)
3
14
0
Order By: Relevance
“…The greater part of research regarding AC-DC superposition and PD is motivated by the AC ripple of voltage source converters of the HVDC transmission systems. Subsequently, typical defects such as voids in polymeric insulators [4][5][6], voids in oil-pressboard arrangements [7] and electrical treeing [8][9][10][11] were investigated. In general, it was found that the AC component dominates the PD behavior and the literature findings can be summarized as follows:…”
Section: Literature Reviewmentioning
confidence: 99%
“…The greater part of research regarding AC-DC superposition and PD is motivated by the AC ripple of voltage source converters of the HVDC transmission systems. Subsequently, typical defects such as voids in polymeric insulators [4][5][6], voids in oil-pressboard arrangements [7] and electrical treeing [8][9][10][11] were investigated. In general, it was found that the AC component dominates the PD behavior and the literature findings can be summarized as follows:…”
Section: Literature Reviewmentioning
confidence: 99%
“…In most of the reports about electrical treeing at industrial frequency, different trends had been found, including periods when negligible PD activity was measured. [1], [20], [53]. The difference between VLF and 50 Hz in the behaviour of times series of PD amplitude could be related with the charge relaxation or charge transport phenomena in PDs [32], [38], [39], [54]: with a lower excitation frequency the electric charge has more time for recombination, which reduces the possibilities of discharge extinction due to deposition of cations in sidewalls of the tree [1].…”
Section: A Pd Time Series and Electrical Tree Growthmentioning
confidence: 99%
“…The probability of the generation of multiple-branch trees decreased with increasing temperature. In [27], a relationship between the electrical tree growth process and PD was found. Different tree structures and growth stages are associated with different PD characteristics.…”
Section: Introductionmentioning
confidence: 99%